Who's Afraid of Those Big Bad Patents? - Linda Shackle (Issues in Science and Technology Librarianship)
The author emphasizes the necessity for science and technology (sci-tech) librarians to be knowledgeable about patents. She points out that most sci-tech librarians teach students about searching the patent literature but adds that there are librarians who are reluctant to do so. She cites that every sci-tech librarians should be capable of using the U.S. Patent and Trademark Office (USPTO) Patents Granted and Patents Applications databases. She notes that patents can be fun and manageable.